"On water" reaction of deactivated anilines with 4-methoxy-3-buten-2-one, an effective butynone surrogate. Issue 47 (18th November 2016) - Jebari, Meriam; Pasturaud, Karine; Picard, Baptiste; Maddaluno, Jacques; Rezgui, Farhat; Chataigner, Isabelle; Legros, Julien
Abstract : ( Z )-Enaminones are easily synthesized from poorly nucleophilic anilines and 4-methoxy-3-buten-2 one (an effective and inexpensive surrogate for 3-butyn-2-one) with impressive "on water" acceleration. Abstract : Poorly nucleophilic aromatic amines (nitroanilines, chloroanilines, etc. ) react readily and selectively with trans -4-methoxy-3-buten-2-one, a convenient, effective and inexpensive surrogate for 3-butyn-2-one, to afford ( Z )-enaminones. The efficiency of the reaction mostly lies in the use of water as a solvent, which enhances the reaction rate by a 45 to 200-fold factor with regard to other media.